2022
DOI: 10.3390/buildings12122206
|View full text |Cite
|
Sign up to set email alerts
|

Construction 4.0 Technologies and Decision-Making: A Systematic Review and Gap Analysis

Abstract: Construction 4.0 involves implementing advanced technologies in construction projects to achieve higher productivity, safety, and sustainability. However, architecture, engineering, and construction (AEC) professionals are reluctant to adopt Construction 4.0 technologies. Lack of information on Construction 4.0 technologies and poor decision-making lead to the issue being unresolved. As a result, the following research question emerged: What are the current trends and research gaps in the existing research on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This expansive review underscores the transformative potential of AI-driven technologies in revolutionizing construction practices and propelling the industry towards a digitally integrated future. Shafei, et al [19] examine the integration of Construction 4.0 technologies and decision-making processes. Their systematic review identifies gaps in the prior research and underscores the potential of Industry 4.0 to positively impact sustainability in construction.…”
Section: Background 21 Industry 40 In Construction Industrymentioning
confidence: 99%
“…This expansive review underscores the transformative potential of AI-driven technologies in revolutionizing construction practices and propelling the industry towards a digitally integrated future. Shafei, et al [19] examine the integration of Construction 4.0 technologies and decision-making processes. Their systematic review identifies gaps in the prior research and underscores the potential of Industry 4.0 to positively impact sustainability in construction.…”
Section: Background 21 Industry 40 In Construction Industrymentioning
confidence: 99%
“…The field of big data analytics involves using advanced computational and statistical techniques to analyze vast amounts of digital information with the aim of extracting valuable knowledge that can be used for decision-making (Lu, Lai, & Tse, 2018). With the increasing availability of data from various sources, big data analytics can be leveraged to extract valuable insights for cost management (Shafei et al, 2022). By analysing large volumes of cost data, patterns, trends, and cost drivers can be identified, enabling more accurate cost estimation, risk assessment, and cost control strategies.…”
Section: Big Data Analyticsmentioning
confidence: 99%
“…Several research initiatives were covered in a study on the integration of Industry 4.0 to increase sustainability performance [6]. Prior research revealed that IR4.0 might assist construction organizations in increasing productivity [7]. As mentioned by the World Economic Forum [8], full digitalization in nonresidential building will result in yearly cost savings from 13 to 21% in the construction phase and from 10 to 17% in the operations phase globally during a decade.…”
Section: Introductionmentioning
confidence: 99%